Protocol for a 20-year follow-up after a randomized controlled trial of a Mediterranean diet in pregnancy: maternal and offspring risk factors for cardiovascular disease - Troensegaard, Hannibal; Khoury, Janette; Westerberg, Ane C.; Tonstad, Serena; Roeters van Lennep, Jeanine; Veierød, Marit B.; Iversen, Per Ole; Holven, Kirsten B.; Retterstøl, Kjetil (Frontiers in Pediatrics, 2023)
Background Inadequate maternal diet during pregnancy can impair offspring health and may increase the risk of cardiovascular disease later in life. The purpose of the proposed study is to assess risk factors for cardiovascular disease among mothers and their offspring 20 years after they participated in a Mediterranean diet intervention trial during pregnancy. Methods The "Cardiovascular Risk Reduction Diet In Pregnancy" (CARRDIP) study was a randomized controlled trial performed in 1999-2001. Participants were randomized to adhere to either a Mediterranean diet or their regular diet during pregnancy. An extensive amount of data, such as diet information, ultrasound measurements, anthropometry, and biomarkers from these mothers during pregnancy and their offspring in the neonatal period was collected. The mother-offspring pairs (n=269) from the CARRDIP study will be invited to a clinical examination and blood sample collection. This follow-up study, conducted 20 years after the original CARRDIP study, will investigate cardiovascular risk factors in mothers and offspring. The primary outcome will be offspring blood pressure. Additionally, the study will explore various aspects related to cardiovascular health, including metabolic and inflammatory status, clinical history, and body composition of the participants. Discussion Previous studies investigating the effects of nutrition during pregnancy on maternal and offspring health have been either observational, animal studies or randomized controlled trials with follow up of less than 5 years.This project aims to study the long-term effects of dietary intervention during pregnancy on maternal and offspring cardiovascular risk markers. The trial is registered in Clinicaltrials.gov (ID: NCT05030922).